Organic photovoltaic cells with HTL layer based on conductive polymers - Amponsah, Bright (Univerzita Pardubice, 2024)
This thesis is divided into a theoretical and an experimental part. The theoretical part deals with organic photovoltaics and describes different materials together with the literature review and description of different types of structures used in the organic photovoltaic cell. Further, it focuses on characterization methods used for organic photovoltaic cells. The main topic of this thesis then becomes parameters for photovoltaic devices such as open circuit voltage, short current, fill factor, and power conversion efficiency. Finally, the theoretical part mentions some picked technologies of deposition/preparation of organic photovoltaic solar cells and experimental methods for their evaluation.
Keywords: organic photovoltaics; PEDOT: PSS; photovoltaic parameters; ellipsometry